Pelatihan Inovasi Kantong Development Screening One No Day untuk Deteksi Dini Perkembangan Balita Bagi Kader Posyandu: One No Day Development Screening Pocket Innovation Training for Early Detection of Toddler Development for Posyandu Cadres - Hapsari, Wanodya; Yuliani, Diki Retno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Around 9.4% of children have developmental disabilities. As many as 91.2% of mothers stimulate their children well, their child’s development will be age-appropriate. Posyandu cadres have a role in detecting developmental disorders, so it is necessary to carry out training for posyandu cadres to detect toddlers’ development. It is hoped that after this training, cadres can pass it on to parents of toddlers. This community service takes the form of One No Day Screening Development Pocket Innovation Training and Mentoring for Posyandu Cadres in Karangtengah Baturraden Village, Banyumas, so that they can detect early development of toddlers. Two lecturers and three students conducted this activity using lecture, discussion, and practice methods. The object of this service activity is 30 posyandu cadres in Karangtengah Village. Empowering cadres were chosen for this activity using educational media, a one no day screening development bag. The training activities carried out were: opening, speech from the midwife at the Baturraden 1 Health Center, pretest, delivery of material from the resource person, discussion, rest, the practice of using the one no day screening development bag innovation by posyandu cadres, post-test, closing. The evaluation in this community service is a question and answer and post-test carried out after the activity is completed. The training results showed that cadres’ knowledge before participating was good at 60%, while for sufficient knowledge, it was 26.7% and 13.3% poor. After participating in the training, the cadres’ knowledge was good at 93.3%, and 6.7% had sufficient knowledge.